Observations of Resource Use by the Threatened Diana Fritillary Butterfly (Speyeria diana) in the Southern Appalachian Mountains, USA. (23rd September 2013) - Wells, Carrie N.; Smith, Eric A.
Abstract : We present four summers (2006–2009) of field observations of the Diana fritillary, Speyeria diana (Cramer, 1777), throughout the Southern Appalachian Mountains, USA, in the eastern portion of its distribution. We describe our observations of resource use by S. diana in sites located in Georgia, Tennessee, South Carolina, North Carolina, and Virginia. Butterflies imbibed nectar from five genera (>11 species) of flowering plants and also imbibed liquid from dirt roads and horse manure. The majority of butterflies (57%) were observed feeding on milkweed, Asclepias spp., a high-quality nectar-producing plant which is known to be an important resource for many Lepidoptera. We documented 14 species of Viola spp., the larval host plant used by Speyeria, in our survey sites. All butterflies were marked to observe their movement. Recapture rates ranged from 17% to 56%, suggesting that dispersal of S. diana out of suitable habitat was somewhat limited.